The relationship between career planning and employment quality: a study of university students in China - Cai, Xiao-Meng (2018)
The number of university students has been increasing these years since China introduced the policy of expanding enrollment in universities, with the number of students rising from 1.01 million in 1999 to more than 8 million in 2018. During this period, great changes have taken place in the domestic and international economic situation. Under the influence of various uncertainties, the employment problem of university students has become increasingly prominent. In addition to the previous employment issues of concern, the employment quality problem also gradually caused the extensive concern of the society, and the job satisfaction is one of the important index to measure the quality of university students' employment. Previous studies have tended to focus on the connotation of graduates' employment satisfaction and the composition of influencing factors, and less attention has been paid to the influence of career planning behavior on graduates' employment satisfaction. With the development of Chinese education, this dissertation will comprehensively to measure university students employment quality, so that to help society have a comprehensive understanding of university students' employment and university students career planning in advance, identify a number of key problems of the employment of various universities as well. Through the solution of the problem to comprehensively improving the quality of university students' employment, it could be considered to promote Chinese education reform and sustainable economic development in China.